Supercritical water oxidation of p-aminonaphthalenesulfonic acid and enhancement by Fenton agent - Liu, Huan (Environmental technology, 2020)
The introduction of Fe2+ into supercritical water oxidation (SCWO) and the formation of Fenton reagent with oxidant H2O2 form a new environment, namely, supercritical Fenton oxidation (SCFO) environment. p-Aminonaphthalenesulfonic acid was selected as the typical organic pollutant to explore the effects of temperature, oxidant multiple, reaction time and Fenton conditions on the TOC removal rate. SCFO showed the superiority in the degradation of organic matter compared with the SCWO. The oxidative degradation kinetics of p-aminonaphthalenesulfonic acid in SCFO environment was further explored. Under SCFO condition, the oxidative degradation of p-aminonaphthalene sulfonic acid was consistent with first-order reaction kinetics. The results showed that the activation energy Ea and pre exponential factor k 0 were 39.937 kJ·mol-1 and 1.94 × 104 s-1 respectively